RESERVOIR UNCERTAINTY SIMULATION STUDY FOR GAMMA FIELD GAS INJECTION AND BLOWDOWN OPTIMIZATION - Umar, Khalid
Gamma Field is located in Block B of South Natuna Sea, consisting of five separated reservoirs in three geological zones, and is being produced since 2008 with forty seven percent of the reservoir hydrocarbons located in the Upper Beta Massive West (UBMW) reservoir. UBMW is gas cap with an oil rim reservoir. In order to maximize the value, this reservoir is maintained with gas injection from Gamma-Teta field to effectively sweep the oil and to maintain the reservoir pressure with small portion of gas being exported. As the other gas fields became depleted faster than expected, it was decided to reduce gas injection rate in UBMW and produce more Gamma and Teta gas to increase gas sales volumes. Though UBMW reservoir is considered as a mature reservoir, there are still a lot of uncertainties. The purpose of this study is to recommend the optimum reservoir management scenario by capturing the range of uncertainties that could impact the Estimated Ultimate Recovery and by varying gas injection rate for the remaining years (partially blowing down the gas early). By using the existing base model, we adjust relative permeability and aquifer strength and size within history match tolerance then run forecast with different gas injection scenario to get the optimum scenario. The sensitivity study generate optimum hydrocarbon recovery and project NPV which are presented in the form of a range of values, which is very important for a better decision towards future reservoir management scenario. From this study, it is inferred that stopping gas injection becomes the optimum scenario with addition NPV of 0.35 MMUSD compared to the base case of 40 MMSCFD gas injection.